Building blocks of life: improving nutrition and health outcomes through fortification and breastfeeding in the first 1000 days of a child’s life - Saran, Rohini; Kasar, Jayendra; Jha, Meenakshi; Sahu, Jatindra K.; Babu, Sonu S.; Mutreja, Ankur (Frontiers in Nutrition, 2025)
Micronutrient deficiencies continue to be an important concern in India, particularly among mothers and young children. Food fortification and fortified rice as a scalable and cost-effective solution, has been accepted as a critical intervention to address these deficiencies. Our analysis examines how food fortification can improve the health of mothers and children in India. Focusing on the vital window of first 1,000 days since conception of a child, we examine the benefits of food fortification, the incidence of micronutrient deficiencies, and the incorporation of fortified foods into India’s social safety net program. The analysis emphasizes the importance of successful public-private partnerships, local institutional commitment, and long-term political commitment to the success of fortification programs. We further emphasize that to ensure optimal nutrition during this critical stage, it essential to support breastfeeding, establish human milk banks, and encourage complementary feeding alternatives. Policymakers, program implementers, and stakeholders committed to improving maternal and child health outcomes in India will benefit from our findings.